Management of anemia in patients in the pre- and postoperative period and critically ill patients - E. Yu. Khalikova; B. V. Silaev (Вестник анестезиологии и реаниматологии, 2020)
The objective: to provide information and discuss the most justified and rational ways of anemia management in the perioperative period and in critically ill patients.Results: anemia as a syndrome associated with the perioperative period and critical conditions occurs in patients of the intensive care unit in 30–70% of cases. Currently, there is a clear trend towards restrictive blood transfusion tactics, the individualization of the anemic status of the patient, as well as the personalization of the treatment. Alternative approaches to blood transfusion are encouraged to improve the oxygen transport function of the blood, including the use of iron supplements in adult patients with hypoferric anemia and treatment with drugs that stimulate erythropoiesis.